Impact of indigenous non-Saccharomyces yeasts isolated from Madeira Island vineyards on the formation of ethyl carbamate in the aging of fortified wines - Leça, João Micael (2021)
The impact of selected non-Saccharomyces yeasts on the occurrence of ethyl carbamate (EC) was evaluated. Hanseniaspora uvarum, Starmerella bacillaris, Pichia terricola, Pichia fermentans and Pichia kluyveri isolated from Madeira Island vineyards were inoculated in Tinta Negra musts. Urea, citrulline (Cit) and arginine (Arg) were quantified when the density of musts attained the levels to obtain sweet (1052 5 g/L) and dry (1022 4 g/L) Madeira wines. The urea concentration varied between 1.3 and 5.3 mg/L, Cit from 10.6 to 15.1 mg/L and Arg between 687 and 959 mg/L. P. terricola and S. bacillaris generated lower levels of urea (<2.5 mg/L), Cit (<11.0 mg/L) and Arg (<845.6 mg/L). The five resulting fortified wines, individually fermented by the selected non-Saccharomyces yeast, were exposed to laboratory-accelerated aging at 70 C for 1 month. From the studied yeasts, P. terricola and S. bacillaris revealed a lower potential to form EC (<100 g/L); therefore, both yeasts can be a useful tool for its mitigation in wines